2019
DOI: 10.1021/acs.jmedchem.8b01464
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of New 1-(Aryl-1H-pyrrolyl)(phenyl)methyl-1H-imidazole Derivatives as Antiprotozoal Agents

Abstract: We have designed and synthesized a series of new imidazole-based compounds structurally related to an antiprotozoal agent with nanomolar activity which we identified recently. The new analogues possess micromolar activities against Trypanosoma brucei rhodesiense and Leishmania donovani and nanomolar potency against Plasmodium falciparum. Most of the analogues displayed IC50 within the low nanomolar range against Trypanosoma cruzi, with very high selectivity toward the parasite. Discussion of structure–activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Lycopene is a phytonutrient playing an important role in human health. Indeed, it has long been known for its several biological activities such as antioxidant [ 10 ], anti-inflammation [ 11 ], hypoglycemic [ 12 , 13 ], photoprotection [ 14 ], anti-angiogenesis [ 15 ], anti-parasitic [ 16 , 17 , 18 , 19 ], antiviral [ 20 ] and others. Several studies have also indicated the effect of dietary lycopene in reducing the risk of chronic diseases such as coronary heart disease [ 21 ], being also useful in reducing the oxidative stress in human immunodeficiency virus (HIV)-infected patients under antiretroviral therapy that have less total antioxidant capacity [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene is a phytonutrient playing an important role in human health. Indeed, it has long been known for its several biological activities such as antioxidant [ 10 ], anti-inflammation [ 11 ], hypoglycemic [ 12 , 13 ], photoprotection [ 14 ], anti-angiogenesis [ 15 ], anti-parasitic [ 16 , 17 , 18 , 19 ], antiviral [ 20 ] and others. Several studies have also indicated the effect of dietary lycopene in reducing the risk of chronic diseases such as coronary heart disease [ 21 ], being also useful in reducing the oxidative stress in human immunodeficiency virus (HIV)-infected patients under antiretroviral therapy that have less total antioxidant capacity [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, compound M26 was three times more powerful than the reference drug Chloroquine (CHQ) as well as it possessed high selectivity index (SI = 253) that demonstrated the best anti-plasmodial activity. 36 …”
Section: Anti-microbial Properties Of Imidazole Derivativesmentioning
confidence: 99%
“… 37 Furthermore, compound M26 exhibited the highest bioactivity against all the investigated targets, one of which is enzymes (a score of 0.6) that is consistent with Saccoliti et al study which mentioned the compound works by inhibiting the CYP51 enzyme as a possible mechanism of action. 36 …”
Section: Target Predictions Of Selected Imidazole Derivativesmentioning
confidence: 99%
“…Substituted pyrroles are an interesting class of heterocyclic compounds due to their widespread use both in medical chemistry, and in the chemistry of new materials . For example, 1‐alkyl‐2‐aryl‐4‐(naphthoyl)pyrroles show high affinity for the cannabinoid receptors CB1 and CB2 (JWH series) and 1 H ‐2‐aryl‐4‐aroylpyrroles were used in the synthesis of potential antiprotozoal agents with high biological activity. In addition, pyrroles with an unsubstituted α‐position can be used in the synthesis of BODIPY, which are used in photodynamic therapy of cancer and also in other various fields of organic electronics (Figure ).…”
Section: Figurementioning
confidence: 99%